2020
DOI: 10.1155/2020/9707238
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Comparison of Aneurysmal Subarachnoid Hemorrhage Grading Scales in Angiogram-Negative Subarachnoid Hemorrhage Patients

Abstract: Numerous grading scales have been proposed to predict the outcome of aneurysmal subarachnoid hemorrhage (SAH); however, these have not been validated in angiogram-negative SAH patients. In this study, we aim to validate and compare the aneurysmal SAH grading scales in angiogram-negative SAH patients. There were 190 angiogram-negative SAH patients analyzed from January 2014 to December 2015. The outcomes were measured by delayed cerebral ischemia (DCI) and poor outcome (defined as modified Rankin Scale (mRS) 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…At the baseline (i.e., in the acute stage of stroke), the following basic data were collected. Social-demographic and clinical data were collected from all enrolled participants in the acute stage of their stroke, including age, sex, living area (i.e., urban and rural), education status (i.e., junior high school and lower, senior high school and higher), marital status (i.e., married, unmarried, divorced, and widowed), having medical insurance (yes or no), monthly income (>6,000 Yuan, ≤6,000 Yuan), smoke and drink dependence (yes or no), hypertension (yes or no), diabetes (yes or no), atrial fibrillation (yes or no), the National Institute of Health Stroke Scale (NIHSS) [ 20 ], the modified Rankin Scale (mRS) [ 21 ], the Barthel Index (BI), infarct location (i.e., cortex, white matter lesions, basal ganglia + thalamus, brain stem, and cerebellum) [ 22 , 23 ], and infarct size (≥20 vs. <20 mm 3 ) calculated in three days after stroke onset by manually delineating the hypodense infarcted area(s) on hyperintense area(s) on axial diffusion weighted imaging slices on magnetic resonance imaging (MRI) [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the baseline (i.e., in the acute stage of stroke), the following basic data were collected. Social-demographic and clinical data were collected from all enrolled participants in the acute stage of their stroke, including age, sex, living area (i.e., urban and rural), education status (i.e., junior high school and lower, senior high school and higher), marital status (i.e., married, unmarried, divorced, and widowed), having medical insurance (yes or no), monthly income (>6,000 Yuan, ≤6,000 Yuan), smoke and drink dependence (yes or no), hypertension (yes or no), diabetes (yes or no), atrial fibrillation (yes or no), the National Institute of Health Stroke Scale (NIHSS) [ 20 ], the modified Rankin Scale (mRS) [ 21 ], the Barthel Index (BI), infarct location (i.e., cortex, white matter lesions, basal ganglia + thalamus, brain stem, and cerebellum) [ 22 , 23 ], and infarct size (≥20 vs. <20 mm 3 ) calculated in three days after stroke onset by manually delineating the hypodense infarcted area(s) on hyperintense area(s) on axial diffusion weighted imaging slices on magnetic resonance imaging (MRI) [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…These prognostic grading scores were not initially designed for AN‐SAH patients, but were also commonly used in the clinical assessment and prognostic prediction of AN‐SAH patients due to the lack of standardized evaluation indicators. In our previous study, we compared the prognostic value of several clinical scores in AN‐SAH patients, and demonstrated their favorable adaptation to this type 5 . However, we did not distinguish the difference between PAN‐SAH and NPAN‐SAH, or did we evaluate other significant factors associated with outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…AN‐SAH can be categorized as PAN‐SAH or NPAN‐SAH according to the bleeding patterns 4 . Half of the patients with AN‐SAH were presented with the perimesencephalic type, which is known to present better clinical outcomes and lower rates of vasospasm than those observed with aneurysmal SAH 5 . However, AN‐SAH still accompanied definite incidence of DCI and poor clinical outcomes, especially in patients with the non‐perimesencephalic bleeding pattern 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We only scanned four vessel angiographies in our patients for diagnostic purposes and checked the location and size of cerebral aneurysm. DSA may yield 25% negative results in subarachnoid hemorrhage [17]. In the study conducted by Paez Granda [10], it has been reported that DSA may be mistaken at a rate of 15%.…”
Section: Discussionmentioning
confidence: 99%